(Green) Strategic Orientation, Innovation Capabilities, and (Green) Competitive Advantage in the Coal Mining Industry - Putrady, Arief R; Maulida, Mira (RSF Conference Series: Business, Management and Social Sciences, 2024)
Despite its economic importance, the coal mining industry confronts significant environmental challenges. Indonesia prefers coal to renewables because of its lower cost. This study investigates the influence of green strategic orientation in promoting business model innovation and a green competitive advantage in the coal mining industry. The findings indicate that a green strategy orientation enhances green competitive advantage through innovation capability. Environmental and innovation capabilities are critical for successfully implementing business model innovation. This study identifies significant aspects that contribute to green competitive advantage and business model innovation. While the study offers useful insights, it has practical and managerial consequences for business sustainability in the coal mining industry.